Предмет: Алгебра,
автор: zZRinkZz
(x-3):x^2-6x+9/x+3 при x=-21 . Как решить ?
Ответы
Автор ответа:
0
при делении дробь переворачиваем и будет умножение
(x-3) *(x+3)/(x-3)²=
=(x-3)*(x+3) разделить на
(x-3)² сокращаем на х-3
= (x+3)/(x-3)=(-21+3)/(-21-3)=
= -18/ -24= 0.75
(x-3) *(x+3)/(x-3)²=
=(x-3)*(x+3) разделить на
(x-3)² сокращаем на х-3
= (x+3)/(x-3)=(-21+3)/(-21-3)=
= -18/ -24= 0.75
Похожие вопросы
Предмет: Русский язык,
автор: Aishaexeshka
Предмет: Русский язык,
автор: polinaverner306
Предмет: Литература,
автор: Аноним
Предмет: Физика,
автор: kar720
Предмет: Алгебра,
автор: justdanceandsing